-3.8x-5=-2.9x+4

Simple and best practice solution for -3.8x-5=-2.9x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.8x-5=-2.9x+4 equation:


Simplifying
-3.8x + -5 = -2.9x + 4

Reorder the terms:
-5 + -3.8x = -2.9x + 4

Reorder the terms:
-5 + -3.8x = 4 + -2.9x

Solving
-5 + -3.8x = 4 + -2.9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2.9x' to each side of the equation.
-5 + -3.8x + 2.9x = 4 + -2.9x + 2.9x

Combine like terms: -3.8x + 2.9x = -0.9x
-5 + -0.9x = 4 + -2.9x + 2.9x

Combine like terms: -2.9x + 2.9x = 0.0
-5 + -0.9x = 4 + 0.0
-5 + -0.9x = 4

Add '5' to each side of the equation.
-5 + 5 + -0.9x = 4 + 5

Combine like terms: -5 + 5 = 0
0 + -0.9x = 4 + 5
-0.9x = 4 + 5

Combine like terms: 4 + 5 = 9
-0.9x = 9

Divide each side by '-0.9'.
x = -10

Simplifying
x = -10

See similar equations:

| G(-1)=-2y+2 | | 1/4d-1=7 | | 8+8=-16 | | G(-2)=-3x+8 | | 7/9y-4 | | 3=4(x-7)+2(10-x) | | 4x^3-48x^2+144x+9=0 | | (2/5)(10/2)= | | 9x^3-27x/18x^2 | | 5c-1=5c+6c | | 3.8/x^2=0.7 | | -1=-4t+2r | | -x^2+8.5x+4=0 | | (a^1/2b^1/3)^1/2 | | .3(11x+4)=2.1-(x+8) | | 18-2x=6x+3 | | 9(k+3)+2=11(k-y) | | x^2=81/121 | | (3x-4)(4-2x)=0 | | .7(7x+3)=1.8-(x+9) | | -x+6=-2x-12 | | -(3/x)=9 | | 4(b-2.1)=b+0.6 | | 3(3n-y)+1=31 | | (3r+8)(3r-8)= | | 2x^2-7=59 | | 7y=-4x | | 2(x+4)+2=8x+2(x+2) | | (7x+84)=112 | | 3x+2x-2=4x+x+2 | | -0.2-q=9q | | X*.05833333333=(X-113) |

Equations solver categories